2004
DOI: 10.1089/104454904773819842
|View full text |Cite
|
Sign up to set email alerts
|

High-Affinity Interaction between HIV-1 Vpr and Specific Sequences That Span the C/EBP and Adjacent NF-κB Sites within the HIV-1 LTR Correlate with HIV-1-Associated Dementia

Abstract: Numerous host and viral factors likely participate in the onset and progression of HIV-1-associated dementia (HIVD). Previous studies have suggested that viral gene expression in resident central nervous system (CNS) cells of monocyte/macrophage lineage play a central role in the production of neurotoxic viral proteins and infectious virus, deregulation of cellular gene expression, and/or dysfunction of glial and neuronal cell populations. HIV-1 replication is regulated, in part, by interactions between cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 26 publications
0
42
0
Order By: Relevance
“…The 5 T SNP results in dramatically reduced binding of Sp1, Sp3, and the truncated form of Sp3 [23]. Approximately 5.1% of the patients within this cohort have a SNP within the LTR at C/EBP site I (AGCTTTCTACAA), where there is a C-to-T change at position 3 (3 T) that also results in a knockout binding phenotype [23,25-27,37,38]. Finally, a small number of the patients (1.0%) in the DrexelMed HIV/AIDS Genetic Analysis Cohort have been found to have the 3T5T double variant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 5 T SNP results in dramatically reduced binding of Sp1, Sp3, and the truncated form of Sp3 [23]. Approximately 5.1% of the patients within this cohort have a SNP within the LTR at C/EBP site I (AGCTTTCTACAA), where there is a C-to-T change at position 3 (3 T) that also results in a knockout binding phenotype [23,25-27,37,38]. Finally, a small number of the patients (1.0%) in the DrexelMed HIV/AIDS Genetic Analysis Cohort have been found to have the 3T5T double variant.…”
Section: Resultsmentioning
confidence: 99%
“…This differential regulation may ultimately impact viral replication in both a cell type- and a tissue-specific manner [13,21,34,35] that may impact the course of HIV-1 disease [36]. Due to sequence variation within the LTR, cis -acting transcription factor binding sites in the LTR may be functionally altered during the evolution of quasispecies, resulting in altered promoter activity [20-22] and altered transcription factor binding [23,25-27]. Studies in the pre-HAART era have demonstrated that specific HIV-1 LTR CCAAT/enhancer binding protein (C/EBP) and Sp protein binding site configurations that arise as a consequence of quasispecies evolution, such as a C-to-T SNP at nucleotide position 3 in C/EBP site I within the context of a subtype B consensus sequence binding site (designated 3 T) and the C-to-T change at nucleotide position 5 in Sp binding site III (designated 5 T), were preferentially encountered in patients with more severe disease [23,37] and the brains of patients with HIVD [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, R77Q, a mutant of Vpr, was unable to bind ANT and impaired the induction of apoptosis, indicating the sequence-specific interaction of Vpr with ANT. A recent study demonstrated that Vpr directly binds with high affinity to cellular transcriptional factors during the progression of AIDS (Burdo et al, 2004). This study was also able to correlate the presence of increased numbers of C/EBP sites within HIV-1 long terminal repeats (LTRs), in clinically defined HIV-associated dementia (HAD) patients, compared to non-HAD patients.…”
Section: Introduction V Pr Is a Highly Conserved Human Immunodeficienmentioning
confidence: 83%
“…The association between ␤-catenin signaling and C/EBP activity is particularly interesting, given recent evidence from Burdo et al showing that different regions of the brain contain LTRs with distinct C/EBP binding sites (5). Furthermore, C/EBP sequence variants that bind Vpr with high affinity occur at a higher frequency in brain tissue from patients with HAD (6). In addition to enhancing HIV transcription, excessive C/EBP␤ and C/EBP␦ activity can increase neuroinflammation that contributes to HAND by enhancing production of proinflammatory cytokines such as interleukin-6 (IL-6), IL-1␤, and tumor necrosis factor alpha (TNF-␣) by astrocytes (31).…”
Section: Discussionmentioning
confidence: 99%